Thermo- and pH-Responsive Behavior of Poly(N-isopropylacrylamide)-Block-Poly[(2-dimethylamino)ethyl Methacrylate] - Noverra Mardhatillah Nizardo; Rida Hasna Fadhilah; Ivandini Tribidasari Anggraningrum (Indonesian Journal of Chemistry, 2023)
The influence of poly(2-dimethylamino)ethyl methacrylate (PDMAEMA) block on the thermo- and pH-responsive behavior of poly(N-isopropyl acrylamide)-block-poly[(2-dimethylamino)ethyl methacrylate)] (PNIPAM-b-PDMAEMA) was studied. The block copolymers were synthesized using reversible addition-fragmentation chain transfer (RAFT) polymerization by varying the chain length of the second block (PDMAEMA). 1H-NMR and FTIR spectra confirmed the formation of block copolymers PNIPAM21-b-PDMAEMA2 and PNIPAM21-b-PDMAEMA7 with the corresponding molar masses from the GPC data. Thermo- and pH-responsive behavior of block copolymers was investigated in phosphate buffer with various pHs. Interesting results showed that the hydrophilic carboxyl end group and the hydrophobic dodecyl end group of the RAFT agent affected the resulting phase transition temperature (Tc), while the Tc was found to be low in the acidic environment. Moreover, larger particle sizes of PNIPAM21‑b‑PDMAEMA2 were found with a pH of 9. It is noteworthy, that the resulted block copolymers might have the potential use in a drug delivery system.